Pengaruh Omnichannel Perceived Value dan Omnichannel Integration Quality terhadap Custemer Loyality pada Pengguna Aplikasi Kredivo - Arsya Kurnia Yosifanti; Abdul Yusuf (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine, explain and analyze the effect of Omnichannel Perceived Value and Omnichannel Integration Quality on Customer Loyalty with a case study on Kredivo application users. This research uses quantitative methods with descriptive and verification approaches. The sample used as many as 384 respondents who are users of the Kredivo application using the Isaac and Michael formula with an error rate of 5% and taken using a probability sampling technique using proportionate stratified random sampling. The analytical technique used is the scale range analysis technique and path analysis with the help of the Succesive Internal Method (MSI), the Microsoft Excel 2019 program and the SPSS version 26 software application. The results of this study indicate descriptively that the Omnichannel Perceived Value, Omnichannel Integration Quality and Customer Loyalty variables are in the good category. Based on the results of the verification analysis, the correlation coefficient between Omnichannel Perceived Value and Omnichannel Integration Quality obtained a value of 0.793, which means that both have a strong correlation. The partial effect of Omnichannel Perceived Value on Customer Loyalty is 81.6% while Omnichannel Integration Quality on Customer Loyalty is 13.2%. The simultaneous influence of Omnichannel Perceived Value and Omnichannel Integration Quality on Customer Loyalty obtained a value of 74.3% and the remaining 57.9% was influenced by other variables that were not examined.